Achieving Understanding : Discourse in Intercultural Encounters /: Discourse in Intercultural Encounters. (2014) - Broeder, Peter; Bremer, Katharina; Roberts, Celia; Vasseur, M.-T. (Department Of Linguistics, University Rene Descartes, Paris V, France); Simonot, Margaret (Department Of Arts, Law; Social Sciences, Islington College)
No abstract available